2019
DOI: 10.1097/aud.0000000000000633
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Mandarin-Speaking Children With Cochlear Implants

Abstract: Parents were satisfied with all domains of HRQoL. Almost all domains exhibited rapid progress over the first 3 months of CI use, with education progressing at a slower rate. This research underscores the importance of language rehabilitation by revealing that strengthening language rehabilitation could be an effective means of improving the HRQoL of children with CIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 49 publications
4
36
0
Order By: Relevance
“…The same subdomains had a high level in the study of Huttunen et al (2009), but children after CI with concomitant pathology were included in the sample [ 21 ] making direct comparison difficult. Zhao et al [ 22 ] reported a low rating (3.45) in the ‘communication’ subdomain, consistent with the present study (3.59) [ 22 ]. Zhao et al [ 22 ] speculated that CIs were used for a shorter period than in the study by Kumar et al (2015) [ 22 , 23 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The same subdomains had a high level in the study of Huttunen et al (2009), but children after CI with concomitant pathology were included in the sample [ 21 ] making direct comparison difficult. Zhao et al [ 22 ] reported a low rating (3.45) in the ‘communication’ subdomain, consistent with the present study (3.59) [ 22 ]. Zhao et al [ 22 ] speculated that CIs were used for a shorter period than in the study by Kumar et al (2015) [ 22 , 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, Kumar and colleagues (2015) obtained 3.65 for ‘well-being and happiness’; their highest rating was obtained for ‘communication’ with 3.93 [ 23 ]. Zhao et al [ 22 ] and Byčkova et al [ 20 ] reported the higher rating in ‘social relations’ with 3.72 and 4.05 respectively [ 20 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later studies demonstrated wide-ranging findings. In a piece of research using the Pediatric Quality of Life Inventory, parents of children with CIs reported statistically significant poorer HRQoL in their children (Haukedal, von Koss, Lyxell, & Wie, 2018), whereas other parents using Children with Cochlear Implants: Parental Perspectives were satisfied with HRQoL, especially with the domain of social relations (Zhao et al, 2018). Additionally, in all social-emotional functioning variables of the Strengths and Difficulties Questionnaire (SDQ; Goodman, 1997) there appeared a tendency in which "parents of children with CIs reported better functioning of their children than parents of children with HAs" (Michael, Attias, & Raveh, 2019, p. 29).…”
Section: Family Qol Of Families Raising Children With Cis or Hasmentioning
confidence: 99%
“…Parents of children and adolescents with CIs rated overall HRQoL positively across psychosocial domains (Kumar, Warner-Czyz, Silver, Loy, & Tobey, 2015). Within the parenting styles paradigm, families reported contradictory outcomes HRQoL in their children (Haukedal et al, 2018;Zhao et al, 2018).…”
Section: Family Hrqol Of Parents Raising Children With Cis or Hasmentioning
confidence: 99%